Frequency and Risk Factors of Recurrent Respiratory Tract Infections in Children Attending Pediatric OPD - Rabia Shamshad, Taiba Abbas, Sughra Wahid, Sobia Nawaz, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Recurrent respiratory tract infections (RRTIs) are among the most frequent causes of morbidity in children worldwide, especially in developing countries where environmental and nutritional factors play a major role. Objective: This study aimed to determine the frequency and risk factors of RRTIs among children attending the pediatric outpatient department. Methods: This cross-sectional study was conducted at Children Hospital Multan from October 2022 To May 2023, included 255 children aged 1 to 14 years presenting with respiratory tract infections. Detailed demographic, environmental, and clinical data were collected through structured questionnaires. Relevant laboratory investigations, including hemoglobin and vitamin D levels, were performed. Results: The overall frequency of RRTIs was 69.8%. Most affected children were in the 1–5-year age group (42.4%) and predominantly male (55.7%). Upper respiratory tract infections (URTIs) accounted for 69.7% of cases, while lower respiratory tract infections (LRTIs) made up 30.3%. Significant associations were found between RRTIs and undernutrition (38.4%), vitamin D deficiency (34.1%), and anemia (27.1%). Environmental risk factors such as passive smoking (79.5%), overcrowding (80.9%), and exposure to biomass fuels (83.0%) were strongly linked to recurrent infections (p < 0.05). Behavioral and preventive factors, including incomplete immunization (84.1%), lack of exclusive breastfeeding (78.3%), and daycare attendance (84.7%), were also significantly associated with RRTIs. The highest frequency of infections occurred during the winter season (67.2%). Conclusion: Recurrent respiratory tract infections in children are influenced by a combination of nutritional deficiencies, poor environmental conditions, and inadequate preventive practices. Keywords: Recurrent respiratory tract infections (RRTIs), Patients, Quality of life, Malnutrition, LSTIs.